Enhancing social skills: the impact of advanced physical education program development - Amirudin; Nurdin, Ambia; Zahara; Nugraha, Hendra; Masyitah (Edu Sportivo: Indonesian Journal of Physical Education, 2024)
Background: The cultivation of social behaviour during childhood and adolescence holds paramount importance, serving as a cornerstone for the establishment of robust interpersonal connections in subsequent stages of life, whether transitioning from adolescence to adulthood. Research Objective: This research aims to assess how implementing enhanced physical education influences social interactions and behaviour among adolescents. Methods: The study employed a pretest-posttest control group design, involving experimental and control groups randomly selected from high school students in the City of Aceh. The study’s population was drawn from class X students at a public high school in Aceh City, encompassing 4 classes with a total of 124 students. Cluster random sampling was employed as the sampling technique. The researcher randomly selected one class as the experimental group and another as the control group. The participants included two classes: 30 students from class 10B as the experimental group and 30 students from class 10D as the control group. Thus, the study involved a total of 60 participants. Social behaviour was evaluated using standardised questionnaires measuring various dimensions. The pre-test and post-test data analysis techniques were analysed using a homogeneity test, a normality test, and a Mann-Whitney test using SPSS version 22, with a significance threshold set at p < 0.05. Finding/Result: The results indicate significant improvements in social behaviour among adolescents who underwent the enhanced physical education, sports, and health program compared to the control group. Conclusion: The findings underscore the importance of integrating comprehensive physical education into high school curricula to foster positive social development among adolescents.